Hormesis method for increasing oat straw with a view to viability of direct-seeding systems - Tavares, Leandro Augusto; Sousa, Saulo Fernando; Correia, Tiago; Silva, Paulo Roberto; Velini, Edivaldo (Revista Ciência Agronômica, 2014)
In conservation agriculture, mainly under direct seeding, maintaining the vegetation ground cover is essential, since this serves as a reservoir of nutrients which are slowly released to plants by microorganisms. Some authors have sought to study increases in the amount of straw in the soil, in addition to slowing down the process of decomposition, with hormesis being one of the techniques used. This technique states that all chemical substances are both poisonous and non-poisonous, with only the dosage determining whether they are lethal or not. This study aimed to evaluate the dry weight and agronomic characteristics of a crop of black oat subjected to hormesis. The experimental design was of randomised blocks, with 12 treatments and 4 replications, giving a total of 48 experimental lots. The treatments were: Haloxyfop-R Methyl Ester at dosages of 0.625, 1.25 and 2.50 g ha-1; Glyphosate at dosages of 12.50, 25.00 and 50.00 g ha-1; 2,4-D dimethylamine salt at dosages of 100.00, 200.00 and 300.00 g ha-1; Alterbane at a dosage of 500.00 g ha-1; Salicylic acid at a dose of 100 g ha-1; and a control. It was concluded that for the subdosages under test, the herbicides 2,4-D at medium dosage and Verdict at low dosage were shown to be the best treatments for conserving straw as ground cover under direct seeding.